Sistem Informasi Manajemen Penjualan Berbasis Mern Stack untuk Konveksi Maxsupply Di Depok - Anggio Marsoni; Falah Nurdiansyah; Muhammad Ilyas Faisal; Wasis Haryono (CV. Multi Kreasi Media, 2025)
Digital transformation in business operations emphasizes the need for integrated information systems, including in the garment industry. MaxSupply, a local garment business, requires a web-based sales information system to support more efficient and well-managed business processes. This study aims to design and develop a sales information system that facilitates product management, order processing, and digital payment. The system was developed using a prototyping method, allowing iterative improvements based on user feedback. It was built using the MERN Stack (MongoDB, Express.js, React.js, Node.js) and includes features such as user authentication, product management, transaction processing, and reporting. The results show that the system improves transaction speed and data accuracy, thereby supporting more structured and efficient operations for MaxSupply.